Paris Baguette: Quintessentially French with love from Korea - HAN, Jin K. (Institutional Knowledge at Singapore Management University, 2018)
This case is set in February 2016, when Paris Baguette (PB) has just been declared the winner at the, touted as the most prestigious baking competition in the world held each year in Paris. PB had started operations in 1945 with a small bakery in North Korea. By 2014, it boasted of 3,200 outlets in South Korea, and another 200 plus outlets across China, USA and Southeast Asia. Buoyed by its international appeal, next the company entered France, opening its first store in 2014 and the second store in 2015. Positioned as a ‘premium health conscious brand’, PB quickly found resonance with the French by diligently following traditional baking standards, suitably localising the innovative menu and offering a café-style service. Its success in France was paving the way for further expansion into other European markets. This was significant given that the Korean domestic market was intensely competitive and heavily regulated against corporate bakeries - so future growth in all likelihood could only come from the international operations. The question now is to decide the appropriate strategy for the bakery brand when entering other European markets. Which country or countries should it go to after France? Should it leverage on its selling proposition of ‘French-ness’, or should it find a staple bread specific to each European country and replicate the strategy followed in France? This case is designed for use in undergraduate, postgraduate and executive education classes that discuss internationalisation and market strategies. Through this case, students will have an opportunity to discuss whether a truly global strategy is preferred to one that is localised to each market. Specifically, students will learn about how an Asian brand can succeed in its overseas expansion not only to other Asian markets but also to the developed Western markets.